Elderly Experience Evaluation through Medication Learning Application with Augmented Reality - Alnabit, Nuha; Indriasari Mansor, Evi (International Journal of Engineering and Technology, 2018)
Technology advancement has been providing innovative solutions to assist elderly to overcome many challenges they face when learning about their medication due to their declining abilities. However, due to the lack of proper understanding of elderly experience and poor representation of their requirements, many of these solutions are rejected.  Natural and simple interactions are one of the main features elderly require to adopt technology which can be supported through the integration of augmented reality technology with these solutions. This paper focused on studying elderly interaction with an augmented reality medication learning application and evaluating their experiences as a user from the perspective of visceral, behavioral and reflective levels at an early stage of the development process. The results indicated positive feedbacks with considerations when developing similar application for the future.